Biochemical analysis of force-sensitive responses using a large-scale cell stretch device. Issue 5 (3rd September 2017) - Renner, Derrick J.; Ewald, Makena L.; Kim, Timothy; Yamada, Soichiro
ABSTRACT: Physical force has emerged as a key regulator of tissue homeostasis, and plays an important role in embryogenesis, tissue regeneration, and disease progression. Currently, the details of protein interactions under elevated physical stress are largely missing, therefore, preventing the fundamental, molecular understanding of mechano-transduction. This is in part due to the difficulty isolating large quantities of cell lysates exposed to force-bearing conditions for biochemical analysis. We designed a simple, easy-to-fabricate, large-scale cell stretch device for the analysis of force-sensitive cell responses. Using proximal biotinylation (BioID) analysis or phospho-specific antibodies, we detected force-sensitive biochemical changes in cells exposed to prolonged cyclic substrate stretch. For example, using promiscuous biotin ligase BirA* tagged α-catenin, the biotinylation of myosin IIA increased with stretch, suggesting the close proximity of myosin IIA to α-catenin under a force bearing condition. Furthermore, using phospho-specific antibodies, Akt phosphorylation was reduced upon stretch while Src phosphorylation was unchanged. Interestingly, phosphorylation of GSK3β, a downstream effector of Akt pathway, was also reduced with stretch, while the phosphorylation of other Akt effectors was unchanged. These data suggest that the Akt-GSK3β pathway is force-sensitive. This simple cell stretch device enables biochemical analysis of force-sensitive responses and has potential to uncover molecules underlying mechano-transduction.